2012
DOI: 10.1111/j.1748-8583.2012.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of motivational language in the technologically mediated realm of telecommuters

Abstract: The purpose of the current study was to extend organisational communication scholarship by examining the use of motivating language by supervisors of telecommuters and how motivating language influences telecommuters' perceptions of their supervisors' communication competence and their own communication satisfaction, job satisfaction, and organisational commitment. Participants included 177 full‐time telecommuters from a number of organisations across the US. The current findings indicate that supervisors of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…With the VT leader's support, VT members were kept motivated, interested in and informed about the progress of the project. This is consistent with a study conducted in a telecommuting work setting by Madlock (2013), who found that the empathetic and motivating language used by supervisors influenced employee attitudes, including job satisfaction and organizational commitment. Further, our finding of the constant feedback in the form of direction giving and showing empathy, reinforces the notion of there being a positive link between social support (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…With the VT leader's support, VT members were kept motivated, interested in and informed about the progress of the project. This is consistent with a study conducted in a telecommuting work setting by Madlock (2013), who found that the empathetic and motivating language used by supervisors influenced employee attitudes, including job satisfaction and organizational commitment. Further, our finding of the constant feedback in the form of direction giving and showing empathy, reinforces the notion of there being a positive link between social support (i.e.…”
Section: Discussionsupporting
confidence: 91%
“…For example, managers might incur a lot of cost in setting up monitoring systems (Groen et al, 2018), but the desirable effect of monitoring on work effectiveness was not supported by our data. Managers should instead engage more supportive management practices especially in this extraordinary context, such as communicating with subordinates using motivating language (Madlock, 2013), building trust within the distributed team (Grant et al, 2013), and sharing information rather than close monitoring (Lautsch et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…As with job satisfaction, studies focused exclusively on telecommuters have aimed to understand predictors of commitment—namely, high-quality relationships with coworkers and supervisors, amount of social support received, coworker inclusionary and exclusionary behaviors, and communication satisfaction and competence (Fay & Kline, 2011, 2012; Golden & Veiga, 2008; Madlock, 2013). Similar predictors of organizational identification have been noted, including amount of social support received, amount of stress from interruptions, coworker inclusionary and exclusionary behaviors, and quality of relationships with coworkers (Fay & Kline, 2012; Fonner & Roloff, 2010; Wiesenfeld, Raghuram, & Garud, 2001).…”
Section: Work-related Outcomesmentioning
confidence: 99%